Green Biopolymers and their Nanocomposites - Gnanasekaran, Dhorali (Materials Horizons: From Nature to Nanomaterials, 2019)
This book comprises a collection of chapters on green biopolymer nanocomposites. The book discusses the preparation, properties, and applications of different types of biodegradable polymers. An overview of recent advances in the fabrication of biopolymers nanocomposites from a variety of sources, including organic and inorganic nanomaterials, is presented. The book highlights the importance and impact of eco-friendly green nanocomposites, both environmentally and economically. The contents of this book will prove useful for students, researchers, and professionals working in the field of nanocomposites and green technology. .